2017
DOI: 10.1016/j.aott.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Bicolumnar 90–90 plating of AO 13C type fractures

Abstract: ObjectiveThe aim of this study was to evaluate functional results and complication rate of patients who underwent medial-dorsolateral plating for intra-articular distal humeral fracture (Müller AO type 13C).MethodsTwenty-four patients (14 men, 10 women; mean age: 47 years) with AO type 13C distal humerus fracture were included in the study. Mean follow-up time was 28 months. Nine patients were in 13C1 subgroup, according to AO classification system, 11 patients were categorized as 13C2, and 4 patients were 13C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We found a very high union rate, 98%, with parallel plating. Previous studies have reported a union rate between 87% and 100% [1,15,20,21,[33][34][35][36][37][38][39]. The functional outcomes were good and the majority of patients (75%) ended up in the categories good or excellent according to the MEPS.…”
Section: Discussionmentioning
confidence: 90%
“…We found a very high union rate, 98%, with parallel plating. Previous studies have reported a union rate between 87% and 100% [1,15,20,21,[33][34][35][36][37][38][39]. The functional outcomes were good and the majority of patients (75%) ended up in the categories good or excellent according to the MEPS.…”
Section: Discussionmentioning
confidence: 90%
“…We also had 2 cases of non-union of olecranon osteotomy which is not in line with studies of Coles et al and Kural et al who have stated 100% union rates of olecranon osteotomy. 10,11 Khalid et al concluded that olecranon osteotomy approach is more effective and preferable to triceps sparing approach. 12 Many studies have evaluated the functional outcome of total elbow arthroplasty and claimed it to be a better option mainly in the elderly age group.…”
Section: Males Femalesmentioning
confidence: 99%
“…entitled “Bicolumnar 90–90 plating of AO 13C Type Fractures”. 1 The objective of the study is noteworthy, and we would like to make a few comments about the report.…”
mentioning
confidence: 99%